KONSELING ISLAM DALAM PENDIDIKAN KELUARGA - Deni Putra Ardiyana (Yayasan Pendidikan Islam dan Multikultural, 2022)
Education is an important part of human life. Because through education, humans can learn to recognize their potential, and then use it. so that with it, it will produce benefits both for himself, and broadly for the environment around him. This study discusses the importance of Islamic counseling in the family to resolve the problems that occur. We realize that the ark of marriage is not always able to navigate it calmly and smoothly. After the family is formed, various problems can arise in the family which in turn will become seeds that threaten marital life and result in rift or divorce. Before this happens in the family or family members should try to prevent it by improving relations within the family and sometimes require outside intervention in an effort to help the family overcome the problem.